PENERAPAN PERMAINAN TRADISONAL ENGKLEK DALAM MENINGKATKAN MINAT BELAJAR NUMERASI SISWA MI - Abdurozaq, Moch Bhilal; Rahman, Alvin Yanuar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low levels of interest and numeracy skills among elementary school students, as revealed through initial evaluations and classroom observations. Numeracy learning is still dominated by lecture-based instruction and abstract exercises, which do not align with the developmental characteristics of young learners who require concrete, active, and enjoyable learning experiences. Moreover, the lack of integration of local cultural contexts in numeracy lessons results in students feeling less engaged and emotionally disconnected from the material. Based on these conditions, this research aims to analyze the effectiveness of using the traditional game Engklek as a learning medium to enhance the interest and numeracy skills of second-grade students at MI Miftahul Falah Bandung. This study employed a quantitative approach with a One-Group Pretest–Posttest Design. The participants consisted of 22 students who received numeracy instruction through the Engklek-based learning model. Data were collected using a learning interest questionnaire and a numeracy test administered before and after the intervention. A paired sample t-test was used to determine whether the difference in scores was statistically significant. The findings indicate a significant improvement in both learning interest and numeracy performance. The average pretest score of 74.54 increased to 95 after the intervention. The statistical analysis showed that the t-value exceeded the critical t-table value and the p-value was < 0.05, indicating a significant difference between pretest and posttest results. In addition to academic gains, students demonstrated higher enthusiasm, confidence, and social interaction throughout the learning process.